How do I get the original price if after you discount by 5% the new price is 57

Answers


Related Questions

What is the LCD of 4 7/9 and 2 2/3?
The zeros of the function f(x) =(x+2) to the second power minus 5
Write an equation which sloves for the radius of an object having a circumference of 46 feet
Given a conditional statement p → q, which statement is logically equivalent? ~p → ~q ~q → ~p q → p p → ~q
Opal is collecting data on water levels in different parts of town. She notices that her sample data has a low-value outlier. Which statement must be true?A. Removing the outlier will not change the spread of the graph of the data set.B. Removing the outlier will not change the variance of the data set.C. Removing the outlier will increase the variance of the data set.D. Removing the outlier will decrease the spread of the graph of the data set.

You have 6 different video games. How many different ways can you arrange the games side by side on a​ shelf?

Answers

36 ways to stack 6+6+6+6+6+6

Multiply the problem,

Answers

Answer:

The answer to your question is the letter B

Step-by-step explanation:

Data

                 | 5  0 |   | 2  - 1 |

                 | 3 -5 |   | 2  - 2|

Process

1.- This is the product of two matrices 2 x 2 so the result will be a 2 x 2 matrix.

- Multiply the first row of the first matrix by the first column of the second matrix.

-Multiply the first row of the first matrix by the second column of the second matrix.

- Multiply the second row of the first matrix by the first column of the second matrix.

-Multiply the second row of the first matrix by the second column of the second matrix.

                 | 5  0 |   | 2  - 1 |         | (5 x 2) + (0 x 2)    (5 x -1) + (0 x -2) |

                 | 3 -5 |   | 2  - 2|    =   | (3 x 2) + (-5 x 2)   (3 x -1)  + (-5 x -2)|

                                              =  | 10 + 0    -5 + 0 |

                                                  | 6 - 10     -3 + 10|

                                             = | 10  - 5 |

                                                | -4     7|

What would be the answer if I substituted the x for zero?
plz help!!

Answers

The answer would be -5
The answer would be negative five. Anything multiplied by zero is zero so that cancels the 2x^3, leaving you 0-5. Which is -5. 

PLS
HELP
ILL
GIVE
MORE
IF
ITS
RIGHT

Answers

Answer:

hello its me again and im trying to help you kid

Step-by-step explanation:

The answer to ur question is b

Can someone help me out with this

Answers

Answer:

Step-by-step explanation:

a) 7² + a⁰ = 7*7 + 1 = 49 + 1 = 50

Anything raised to 0 is 1  {Eg: 15⁰ = 1 ,(-k)⁰ = 1}

b) 4³ - 3¹ = 4*4*4 - 3 = 64 - 3 = 61

c) 12x⁶ * 7x⁸ = (12*7)*x⁶⁺⁸ = 84x¹⁴

In exponent multiplication, If x is a rational number and a & b are two integers, then xᵃ * xᵇ = xᵃ⁺ᵇ

d) 49a¹³ ÷ 7a⁸ = (49 ÷ 7) * a¹³⁻⁸ = 7a⁵

In exponent division, If x is a rational number and a & b are two integers, then xᵃ ÷ xᵇ = xᵃ⁻ᵇ

e) (2y³)⁵ = 2⁵*(y³)⁵ = 32y³ˣ⁵ = 32y¹⁵

Find the equation of the circle whose center and radius are given.center ( 7, -3), radius = 7

Answers

Answer:  The required equation of the circle is x^2+y^2-14x+6y+9=0.

Step-by-step explanation:  We are given to find the equation of the circle with center at the point (7, -3) and radius of length 7 units.

We know that

the standard equation of a circle with center at the point (h, k) and radius of length r units is given by

(x-h)^2+(y-k)^2=r^2~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~(i)

For the given circle,

center, (h, k) = (7, -3)  and  radius, r = 7 units.

From equation (i), we get

(x-7)^2+(y-(-3))^2=7^2\n\n\Rightarrow (x-7)^2+(y+3)^2=49\n\n\Rightarrow x^2-14x+49+y^2+6y+9=49\n\n\Rightarrow x^2+y^2-14x+6y+9=0.

Thus, the required equation of the circle is x^2+y^2-14x+6y+9=0.

(x – h)² + (y – k)² = r² 

Fill in the numbers 

(x – 7)² + (y +3)² = 49